Enhancement of FMIPv6 by Utilising Concurent Binding Update Process - Ismat Aldmour; Lelyzar Siregar; Thair Al Dala’in; Rahmat Budiarto (IAES Indonesia Section, 2014)
The world is progressing toward the Mobile Internet Protocol Television (MIPTV) era where people are able to watch television while roaming. The MIPTV technology requires high bandwidth and low latency handover. This paper enhances the binding updates process in the Fast Handover Mobile IPv6 (FMIPv6) to improve its handover process performance in term of secureness and robustness, by implementing concurant binding update process thru the use of the International Mobile Subscriber Identifier (IMSI). Simulation results show that the proposed idea reduces the handover latency to about 63% compared to standard FMIPv6.